2016
DOI: 10.1007/s00464-016-5195-0
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative hypothermia and surgical site infection following peritoneal insufflation with warm, humidified carbon dioxide during laparoscopic colorectal surgery: a cohort study with cost-effectiveness analysis

Abstract: BackgroundSurgical Site Infection (SSI) occurs in 9 % of laparoscopic colorectal surgery. Warming and humidifying carbon dioxide (CO2) used for peritoneal insufflation may protect against SSI by avoiding postoperative hypothermia (itself a risk factor for SSI). This study aimed to assess the impact of CO2 conditioning on postoperative hypothermia and SSI and to perform a cost-effectiveness analysis.MethodsA retrospective cohort study of patients undergoing elective laparoscopic colorectal resection was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 17 publications
(20 reference statements)
2
35
0
2
Order By: Relevance
“…Perioperative hypothermia commonly is defined as a body temperature less than or equal to 36.0° C (≤96.8° F) during the perioperative continuum of care . Multiple studies describe negative outcomes associated with inadvertent hypothermia, including surgical site infection, coagulation dysfunction, increased intraoperative blood loss, sepsis, and mortality . Although the seriousness of postoperative complications varies, one research group found that mortality increased fourfold in patients who had experienced perioperative hypothermia .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perioperative hypothermia commonly is defined as a body temperature less than or equal to 36.0° C (≤96.8° F) during the perioperative continuum of care . Multiple studies describe negative outcomes associated with inadvertent hypothermia, including surgical site infection, coagulation dysfunction, increased intraoperative blood loss, sepsis, and mortality . Although the seriousness of postoperative complications varies, one research group found that mortality increased fourfold in patients who had experienced perioperative hypothermia .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other previous studies have reported that warming and humidifying CO 2 significantly decreases the risk of SSIs, and reduces readmission rates and length of hospital stay. [13,34] This differences may be due to the different types of surgery and insulation measures. Hypothermia results in subcutaneous vasoconstriction, and decreased oxygen tension in this layer at a wound site increases the risk of SSIs.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier data suggest that cold, dry gas can cause structural and biochemical injury to the peritoneal mesothelium, which results in a local inflammatory and cytokine response that may increase postoperative pain, and potentially contribute to adhesion formation, tumor seeding, and systemic progression. [12,13] However, more recent evidence from high quality, randomized controlled trials and a Cochrane meta-analysis have shown no difference in postoperative pain scores or opiate use with warming and humidification. [14,15] Surgical site infections (SSIs) represent up to 20% of all healthcare-associated infections.…”
Section: Introductionmentioning
confidence: 99%
“…Wundinfektionen traten signifikant häufiger in der Kontrollgruppe ohne Erwärmung auf (p = 0,001) [12]). Eine Kohortenstudie mit Kosten-Effektivitäts-Analyse zeigte eine signifikante Reduktion der Inzidenz von Wundheilungsstörungen nach laparoskopischen kolorektalen Resektionen mit Insufflation von befeuchtetem und erwärmtem Kohlendioxid [25].…”
Section: Diskussionunclassified